(3GdOhQ GdWbSi hGdSjGSi ddbH (B((3EjQJ QY(B) (3ai GdeUGOQ GdeUQjI GdbOjeI hOdGdGJg MJi fgGjI GdYUQ GdeJCNQ (B/s - (3,gGdI eMeO aQjO CMeO GdCSeQ s; (3Sdhi CMeO cGeds; (3ejSQI YHOGddg MSjfs; (3ZGOI eUWai YRGes (2024)
(3JJfGhd GdQSGdI OQGSI dbH EjQJ QY hOhQg hOdGdGJg hGdEdgGJ GddGJj Medfg hPdc ef NdGd, JJHY GdHOGjGJ GdJGQjNjI dXghQ GddbH hJCUjdg hJWhQg, GdJYQa Ydi GdEdgGJ GddGJj Medfg, hOQGSI cd ef GdSeGJ GdeTJQcI ddEdgGJ GdeNJdaI GddGJj Medf GddbH heG JeKdg, hegGe GdEdgGJ GdJj GQJHWJ HGddbH hGdOhQ GdWbSj hGdOfjhj hGdSjGSj hGdHMK ai OdGdGJg hcPdc GdWbhS hGdGMJaGdGJ GdOjfjI dMGedGJ dbH (B((3EjQJ QY(B) (3hYdGbJgG HCSWhQI Yjf QY, HfSNgG GdeNJdaI, hGdOhQI GdTeSjI hGdfjdjI hGdMaGX Ydi GdfXGe Gdchfj(B. (3ceG Je GdHMK ai YOe JaQO GdEdgGJ HgPG GddbH(B.s
This thesis presents the title irt-Ra, its role and significance, and the goddesses who hold, through tracing the title emergence, its origins and development, identify the goddesses who hold the title, studying all the common features between them and what they represent. It studies also the goddesses$1 (Btasks which are related to the title, the ritual, and political role and its significance, as well as, the special rituals and religious celebrations of the goddesses with the title and its relation to the myth of the Eye of Ra, in its various versions, the solar and Nile cycles, maintaining the cosmic order and irt Ra as a title not for goddesses only.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B230-240.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdEdgGJs; (3EHfI QYs -- irt Ra -- (3Yjf QYs